1968
DOI: 10.1177/00220345680470051201
|View full text |Cite
|
Sign up to set email alerts
|

Acquisition of Fluoride in Vivo by Enamel from Repeated Topical Sodium Fluoride Applications in a Fluoridated Area: A Preliminary Report

Abstract: Fluoride acquisition by deciduous enamel of 11- to 14-year-old children, living in a fluoridated area, was studied during repeated topical applications of acidulated phosphate fluoride gel drops in plastic mouthpieces. Enamel fluoride progressively increased as the number of treatments increased, reaching a concentration of 1,785 ppm at a depth of 5μ after an average of 56 treatments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1971
1971
1975
1975

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…To increase the amount of permanently bonded F ' in enamel, multiple treatments [Mellberg et al, 1970;D avies, 1973] as well as etching with acids [De P aolo, 1971;G edalia, 1971] have been studied in detail. The use of a single treatment, however, seems to be essential for use and ac ceptance in dental clinics and in the dental health programs.…”
mentioning
confidence: 99%
“…To increase the amount of permanently bonded F ' in enamel, multiple treatments [Mellberg et al, 1970;D avies, 1973] as well as etching with acids [De P aolo, 1971;G edalia, 1971] have been studied in detail. The use of a single treatment, however, seems to be essential for use and ac ceptance in dental clinics and in the dental health programs.…”
mentioning
confidence: 99%
“…Deciduous teeth were collected from all children in the study and submitted to analysis for fluoride by previously described techniques [Mellberg et al, 1968;H eifetz et al, 1970], The procedure essentially consists of etching four thin layers with 0.5 n HC104 from blocks of sound enamel cut from buccal or lingual teeth surfaces (approximately 20 mm2) and analyzing the layers for fluoride and calcium. Etch times were 30, 30, 60 and 120 sec and resulted in layers approximately 10, 12, 20, and 40 «m thick, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Enamel is not of homogeneous composition. Numerous studies have demonstrated the inverse relationship between fluoride content and depth from the surface (BRUDEVOLD, STEADMAN and SMITH, 1960;ISAAC et al, 1958;MELLBERG et al, 1968). Other enamel constituents also demonstrate variable concentrations that appear to be depth dependent (BATTISTONE, FELDMAN and REBA, 1967;SOREMARK and GRIN, 1966).…”
Section: Summary-techniquesmentioning
confidence: 99%